The Consequences Received By Traders Of Imported Used Clothing (Thrift) With The Existence Of The Regulation Of The Minister Of Trade On The Prohibition Of Imported Used Clothing In The Central Banjarmasin Sub-District - Linggahwati, Alifya Endah (Sharia Journal and Education Center Publishing, 2024)
Abstract The activity of buying and selling imported used clothing (thrift) that is still found in Central Banjarmasin District is the reason for this research. The activities carried out by thrift merchants are contrary to the policy on the prohibition of imported used clothing in Indonesia. Due to the various impacts on humans and the environment, the import of used clothing is illegal in Indonesia. However, the attitude of imported used clothing traders who oppose this regulation makes them of course have consequences that will be accepted. This research uses empirical legal research methods with a sociological juridical approach and descriptive qualitative research. The results of the research obtained are, first, the implementation of the regulation on the prohibition of imported used clothing has not been carried out optimally because there are several obstacles such as differences in interpreting existing regulations, inadequate facilities and infrastructure, difficulty in knowing the origin of used clothing and rejection by imported used clothing traders (thrift). Second, the consequences received by used clothing traders are not so great because the consequences obtained are only temporary so that traders can still carry out buying and selling activities of imported used clothing (thrift) in Central Banjarmasin District. Keywords: Consequences, Traders of Imported Used Clothes (Thrift), Regulation on the Prohibition of Imported Used Clothes Abstrak Aktivitas jual beli pakaian bekas impor (thrift) yang masih ditemui di Kecamatan Banjarmasin Tengah menjadi alasan adanya penelitian ini. Aktivitas yang dilakukan oleh pedagang pakaian bekas impor (thrift) sangat bertentangan dari adanya kebijakan tentang larangan impor pakaian bekas di Indonesia. Dikarenakan menimbulkan berbagai dampak terhadap manusia hingga lingkungan, impor pakaian bekas menjadi hal yang ilegal di Indonesia. Namun, sikap pedagang pakaian bekas impor yang menentang peraturan ini membuat mereka tentu saja memiliki konsekuensi yang akan diterima. Penelitian ini menggunakan metode penelitian hukum empiris dengan pendekatan yuridis sosiologis dan sifat penelitian deskriptif kualitatif. Hasil penelitian yang didapatkan yaitu, pertama, pelaksanaan peraturan larangan impor pakaian bekas belum dilakukan dengan maksimal karena terdapat beberapa kendala seperti perbedaan dalam memaknai peraturan yang ada, sarana dan prasarana yang belum memadai, kesulitan dalam mengetahui asal pakaian bekas serta adanya penolakan oleh pedagang pakaian bekas impor (thrift). Kedua, konsekuensi yang diterima oleh pedagang pakaian bekas tidak begitu besar karena konsekuensi yang didapatkan hanya bersifat sementara sehingga pedagang masih dapat melakukan aktivitas jual beli pakaian bekas impor (thrift) di Kecamatan Banjarmasin Tengah. Kata Kunci: Konsekuensi, Pedagang Pakaian Bekas Impor (Thrift), Peraturan Larangan Impor Pakaian Bekas